Implementasi Kuliah Kerja Nyata Multibidang Berbasis Identifikasi Kebutuhan untuk Pemberdayaan Masyarakat Desa Pandu, Kecamatan Cerme, Kabupaten Gresik - Miftahul Habibil Fajri; Hilal Zakaria; Rinanda Aprilia Zahro; Muhammad Syahrul; Rismawati Rismawati; Taufik Nurbeni; Nurulita Ramadhani; Ahmad Nazariel Maulana Muzaky; Muhammad Nur Nafik; Gunadi Gunadi; Siti Aisyah Azzahra Widayat; Ayu Lumunturuningtyas; Arif Budiharjo (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2026)
Community service is an implementation of the Tri Dharma of Higher Education, serving as a bridge between academic knowledge and the actual needs of society through relevant, participatory, and sustainable empowerment programs. However, the implementation of Kuliah Kerja Nyata (KKN) frequently encounters challenges because program planning is not always based on a systematic assessment of community needs, resulting in interventions that are less effective in addressing local issues. This article aims to describe the implementation of a multidisciplinary Kuliah Kerja Nyata (KKN) program based on community needs assessment as a strategy for community empowerment in Pandu Village, Cerme District, Gresik Regency. The community service program adopted a community needs assessment approach consisting of five stages: needs identification through field observations, interviews, focus group discussions with community members, and coordination with the village government; needs analysis using the Strengths, Weaknesses, Opportunities, and Threats (SWOT) framework; development of a Planning of Action (PoA); program implementation; and monitoring and evaluation. The program covered four major areas: economic development through business branding assistance and business banner design for micro, small, and medium enterprises (MSMEs); education through English learning activities and the development of educational learning media for early childhood students; social development through awareness campaigns and the preparation of educational modules on drug abuse prevention; and governance through coordination with the village government and partner institutions. The results demonstrated that a needs assessment–based approach produced programs that were better aligned with community conditions and priorities. Collaboration among the village government, educational institutions, MSMEs, university students, and community members enhanced program effectiveness, as reflected in the development of MSME promotional media, educational learning materials, educational modules, and increased community participation throughout the activities. Therefore, a community needs assessment–based approach proved effective in improving the relevance, effectiveness, and sustainability of community service programs.